La science comme formation institutionnelle dans The New Era et Journey to Utopia - Nathaniel Isaacson (MONDE CHINOIS NOUVELLE ASIE, 2018)
The emergence of science fiction in China was conditioned by an awareness of the potential complicity of the genre with the imperial imagination, and a desire to use the genre as a means of creating counter narratives. Late Qing audiences sought mediation as their nation was transformed from hegemon into a crumbling backwater. Late Qing intellectuals agonized over how to reconcile westernization, modernization, and the adoption of foreign technologies with a Chinese epistemological framework. Long before critiques of Orientalism had gained traction as a cornerstone of postcolonial studies, Biheguan Zhuren’s The New Era (1908), and Xiaoran Yusheng’s Journey to Utopia (1906), expressed an implicit understanding that Orientalism profoundly conditioned early 20th century geopolitics. In this paper, highlight a particular phenomenon in late Qing science fiction: insofar as SF addressed the significance of “science,” it was often the case that late Qing intellectuals depicted science as the product of specific modern institutional formations. That is to say, The New Era and Journey to Utopia feature wondrous descriptions of imaginary technologies, but both novels also pay close attention to the abstract and concrete institutions dedicated to the production and dissemination of knowledge, and modes of social organization, especially time. These institutions and social structures featured prominently in late Qing SF as crucial axes in a social Darwinian contest for national survival.